1984
DOI: 10.1159/000225803
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Alkyllysophospholipid ET-18-OCH<sub>3</sub> on Methylnitrosourea-induced Rat Mammary Carcinomas

Abstract: This study describes the efficacy of the alkyllysophospholipid 1-octadecyl-2-methoxy-Sn-rac-glycero-3-phosphocholine (ET-18-OCH3) in inhibiting the growth of methylnitrosourea-induced mammary carcinomas in Sprague-Dawley rats. In experiment A 2 x 10 mg/kg Et-18-OCH3 were administered daily for 10 weeks prior to manifestation of mammary carcinomas which resulted in a significant inhibition of median tumor number and median tumor volume per rat. Treatment of established tumors (experiment B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…in BD-VI rats [323]. Oral administration of 10 mg/kg ET-18-OCH 3 twice daily inhibited partially the growth of methylnitrosourea-induced mammary carcinomas in Sprague-Dawley rats [324]. This treatment was well tolerated without symptoms of toxicity.…”
Section: Assays In Animal Modelsmentioning
confidence: 87%
“…in BD-VI rats [323]. Oral administration of 10 mg/kg ET-18-OCH 3 twice daily inhibited partially the growth of methylnitrosourea-induced mammary carcinomas in Sprague-Dawley rats [324]. This treatment was well tolerated without symptoms of toxicity.…”
Section: Assays In Animal Modelsmentioning
confidence: 87%
“…and alkylphosphocholines represent two related classes of anticancer agents that target the cell membrane (4,12,19). Selective sensitivity of chemically induced, autochthonous mammary carcinoma to these agents has been established recently (6,10,16). This sensitivity might be due to several reasons including the finding that MNU-and 7,12-dimethylbenzanthracene-induced rat mammary carcinomas are known BT AL to contain a mutated cH-ras oncogene resulting in the expression of an altered G-protein which is located in the membrane and involved in signal transduction (3).…”
Section: Alkyllysophospholipidsmentioning
confidence: 99%
“…As early as the late 1960s, Hansjörg Eibl replaced the glycerol-linked ester bond at position C1 of LysoPC by an ether linkage, and added another ether-linked methyl group at the C2 position. The resulting ether lipid, 1-O-octadecyl-2-O-methyl-rac-glycero-3-phosphocholine (edelfosine, ET-18-OCH3; Figure 16.1; Berger et al, 1984), was found to be a potent immune modulator and an effective inhibitor of tumor cell proliferation. The antineoplastic properties of edelfosine have been evaluated in a broad panel of tumor and normal cells, as well as in mouse and rat tumor models, showing a high degree of selectivity towards tumor cells.…”
Section: Introductionmentioning
confidence: 99%